ASU - Språkbanken Text (University of Gothenburg, 2024)
For access please contact Niclas Abrahamsson.

För åtkomst kontakta Niclas Abrahamsson.
ASU
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik